2017
DOI: 10.1186/s13049-017-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a large trauma center: impact of blunt chest trauma in polytrauma patients—still a relevant problem?

Abstract: BackgroundThoracic trauma is the third most common cause of death after abdominal injury and head trauma in polytrauma patients. The purpose of this study was to investigate epidemiological data, treatment and outcome of polytrauma patients with blunt chest trauma in order to help improve management, prevent complications and decrease polytrauma patients’ mortality.MethodsIn this retrospective study we included all polytrauma patients with blunt chest trauma admitted to our tertiary care center emergency depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
82
3
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 23 publications
9
82
3
16
Order By: Relevance
“…Common associated injuries include spine injuries, extremity fractures, abdominal injuries, and head trauma. [17] In the study conducted by Chrysou et al, [8] the most common co-existing extra-thoracic injuries were extremity fractures, spine injuries, and head trauma, with an incidence rate of 76.4%, 53.6%, and 37.3%, respectively. Freixinet et al [12] reported a rate of 19.1% for extra-thoracic trauma, and mentioned that limb fracture was the most common pathology, with an incidence of 28.7%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Common associated injuries include spine injuries, extremity fractures, abdominal injuries, and head trauma. [17] In the study conducted by Chrysou et al, [8] the most common co-existing extra-thoracic injuries were extremity fractures, spine injuries, and head trauma, with an incidence rate of 76.4%, 53.6%, and 37.3%, respectively. Freixinet et al [12] reported a rate of 19.1% for extra-thoracic trauma, and mentioned that limb fracture was the most common pathology, with an incidence of 28.7%.…”
Section: Discussionmentioning
confidence: 98%
“…[7] The incidence of rib fracture in all trauma cases varies in the range of 10% to 40%. [1,4] Chrysou et al [8] reported that rib fractures comprised the largest group of thoracic injuries, with a rate of 86.4%. The incidence of bilateral rib fractures has been reported to be 22.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have usually targeted treatments of severe blunt chest trauma by managing the hemothorax or pneumothorax [21][22][23]. Initially, fractured ribs were not the main target of treatment in our hospital [23].…”
Section: Discussionmentioning
confidence: 97%
“…It can concern traumatic situation , malignant effusion , or postoperative management . In the emergency department, more than 50% of patients presenting a thoracic injury require a thoracostomy . Complications can occur during the procedure or during chest tube maintenance with a range from 5% to 10% and may concern lung, heart, intercostal pedicle, diaphragm, spleen, and bowel and the list is not exhaustive .…”
Section: Discussionmentioning
confidence: 99%